STRUKTUR BATUAN PENYUSUN DESA PADA’ELO KECAMATAN MALLAWA KABUPATEN MAROS - Musriadi, Musriadi; Wahyuni, Ayusari; Zelviani, Sri; Trihendriansyah, Trihendriansyah; Lestari, Utari (Universitas Islam Negeri Alauddin Makassar, 2019)
This field study aims to look at the structure of rock layers and formations in the Mallawa area of Maros Regency. The method used in this studi is sampling at two points where these two points are estimated to have alignment on the layer. This method is a method of observation, direct measurement, and rock sampling at each point. From . This is obtained by several rock samples from each point which are then tested using water which serves to test the permeability and porosity of rock samples, while the hardness of the rock is tested by giving a scratch on the sample. From the research it was concluded that in general the rock structure in Pada’ Elo, Kecamatan. Mallawa, Maros Regency is composed of sedimentary rock formations.